(untitled) (Journal on studies and research of academic knowledge, 2024)
Regional development is a process of structural socio-economic and environmental changes, the main objective of which is to improve the well-being of the population of the territory and to reduce social and economic inequality within the framework of the sustainable development approach. The aim of the research is to describe aspects of regional development. For this purpose, a qualitative approach methodology of documentary and descriptive review was used. The data collection technique was a literature search in ScienceDirect databases, and grounded theory was used for data analysis. The main results show that regional development has key aspects, the main ones being foreign direct investment because it provides capital, technology and employment, another is integrated trade logistics, which facilitates imports and exports, support for SMEs with public financing policies and incentive programmes, digitalisation of SMEs, with the adoption of e-commerce in their different processes, and finally, the relationship between universities and companies with the transfer of knowledge and technology. Further research is recommended to study aspects of regional development in border areas